Haiti : Enhanced Initiative for Heavily Indebted Poor Countries; Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses Haiti's progress under the Enhanced Initiative for Heavily Indebted Poor Countries. Substantial advances have been made toward meeting the four triggers not fully implemented, and the authorities are committed to further progress in the near future. These triggers relate to publication of audited government accounts, implementation of a new procurement law, education funding, teacher training and school inspections, and increasing immunization rates. Haiti's parliament passed a new procurement law in June 2009, which is in line with international best practices.